2020
DOI: 10.1002/cctc.201902306
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Steam Reforming of Natural Gas over a New Ni Exsolved Ruddlesden‐Popper Manganite in SOFC Anode Conditions

Abstract: The catalytic behavior of the new Ni exsolved Ruddlesden‐Popper (RP) manganite (La1.5Sr1.5Mn1.5Ni0.5O7) for the reforming reaction was studied. The material was synthesized by the Pechini method and reduced to induce the formation of two phases: n=1 RP structure LaSrMnO4 decorated with Ni nanoparticles. Ni impregnation on (La,Sr)2MnO4 ceramic support of similar composition was also prepared for comparison. The catalytic measurements were carried out in a reduction‐reaction process with low steam to carbon cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 111 publications
(238 reference statements)
1
10
0
Order By: Relevance
“…As a result of thermal treatments, a partial segregation of Fe and Co from the bulk of the perovskite moved to the surface and combined with the Ni to form fine embedded nanoparticles on the surface of the depleted LSFCO. The resulting phases were a Ruddlesden-Popper-type structure [41,54,55] and a solid oxide solution between Ni, Fe, and Co (i.e., α-Fe100−y−zCoyNizOx oxide) [56,57]. This exotic material was extensively investigated by the authors of this work, and is reported in other papers.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…As a result of thermal treatments, a partial segregation of Fe and Co from the bulk of the perovskite moved to the surface and combined with the Ni to form fine embedded nanoparticles on the surface of the depleted LSFCO. The resulting phases were a Ruddlesden-Popper-type structure [41,54,55] and a solid oxide solution between Ni, Fe, and Co (i.e., α-Fe100−y−zCoyNizOx oxide) [56,57]. This exotic material was extensively investigated by the authors of this work, and is reported in other papers.…”
Section: Methodsmentioning
confidence: 84%
“…However, a new class of materials corresponding to "exsolved perovskite" has been recently used as fuel electrodes for SOC cells [37][38][39][40][41][42][43]. These materials have a unique morphology based on a substrate with mixed ionic and electronic conductivity (MIEC) supporting encapsulated fine particles that originate from the segregation of metals from the MIEC's bulk [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Both approaches have been addressed to promote a similar distribution of fine exsolved particles on the surface. It was reported that the first method should be preferred in case of high risks for their coarsening [ 70 ].…”
Section: Surface Exsolution and Physicochemical Studiesmentioning
confidence: 99%
“…Both approaches have been addressed to promote a similar distribution of fine exsolved particles on the surface. It was reported that the first method should be preferred in case of high risks for their coarsening [63].…”
Section: Surface Exsolution and Physico-chemical Studiesmentioning
confidence: 99%